Soluble modulators of intermolecular interactions in proteins and lipid rafts - Lane, Jordan Samuel (2018)
The nonspecific binding of proteins to various biological and non-biological surfaces has limited the potential of several detection techniques such as surface plasmon resonance (SPR), Luminex and ELISA (among others). Plasma proteins have been shown to decrease the sensitivity of instruments when working with complex fluids such as blood samples. This study examines the binding properties of several plasma proteins to a range of surfaces and utilises reagents in the media to eliminate the nonspecific binding of the plasma proteins. This has created a set of conditions that can reduce the nonspecific binding interaction, without affecting the specific interactions which the various techniques measure. These mechanisms were then applied to the assembly/disassembly of membrane microdomains. Membrane microdomains have been shown to be affected by from several factors such as acyl-chain length and temperature. This study demonstrates how reagents in the media can affect the assembly of these domains. We proposed a novel mechanism for the regulation of the domains, in which the reagents alter the intermolecular interactions between lipid head groups by altering the water network around these domains to promote domain assembly. These results that could have significant ramifications for the functional characterisation of membrane microdomains and the proteins that are known to associate with them. Finally, membrane binding affinity and kinetics of different polypeptides with various lipid membrane composition were characterised and resultant microdomains were monitored. Demonstrating how the previously uncontrolled, soluble factors in a model system can control the intermolecular interactions that occur in the system that is being measured.